An introduction to aspects of thermodynamics and kinetics relevant to materials science - Machlin, E. S. (Elsevier, 2007)
This book is based on a set of notes developed over many years for an introductory course taught to seniors and entering graduate students in materials science. An Introduction to Aspects of Thermodynamics and Kinetics Relevant to Materials Science is about the application of thermodynamics and kinetics to solve problems within Materials Science. Emphasis is to provide a physical understanding of the phenomenon under discussion, with the mathematics presented as a guide.